Analisis Komponen Angin Zonal dan Meridional Sebagai Penentu Awal Musim di Wilayah Tana Toraja - Herniella Tiara Utami; Muhammad Arsyad; Husain Husain (Universitas Andalas, 2024)
The determination of the onset of season typically utilizes the rainfall distribution pattern during the climatological period in the form of a bar graph. However, according to previous research, the prediction of the onset of the season can also use the components of Zonal and Meridional winds. There hasn't been much research related to the onset of season in Tana Toraja; therefore, this study aims to determine the profile of Zonal and Meridional winds at the 850 mb level and their relation to the onset of season in Tana Toraja during the climatology period from 1998 to 2022 (25 years) as well as during El Niño and La Niña events. Reference data for this analysis is sourced from daily precipitation records from the Toraja Meteorological Station and daily Zonal and Meridional wind array model data from the European Centre for Medium-Range Weather Forecasts (ECMWF). The collected data is then visualized through maps and graphs, followed by spatial and descriptive analysis for the klimatologi period, El Niño, and La Niña events. The analysis findings reveal that the rainfall pattern in Tana Toraja is significantly influenced by monsoonal winds, particularly characterized by the prevalence of westerly Zonal winds during the rainy season. The onset of the rainy season typically occurs in early July, with the peak of the rainy season usually observed from mid-March to mid-April. Zonal winds during El Niño and La Niña events notably impact rainfall accumulation in the Tana Toraja region, resulting in variations in the strength of Zonal and Meridional winds.